Effectiveness of Urate-Lowering Therapy for Renal Function in Patients With Chronic Kidney Disease: A Meta-Analysis of Randomized Clinical Trials - Liang, Xiuping; Liu, Xiang; Li, Duohui; Qin, Wei; Liu, Yi (Frontiers in Pharmacology, 2022)
Abstract Background and Objective: Hyperuricemia is closely related to chronic kidney disease (CKD). The effects of urate-lowering therapy (ULT) on renal outcomes are uncertain, and whether it is warranted in CKD patients is currently unclear. The aim of our meta-analysis of randomized clinical trials (RCTs) was to assess the effectiveness and safety of ULT for improving kidney function in patients with CKD. Methods: RCTs were retrieved from the PubMed, Embase, MEDLINE and Cochrane Central Register of Controlled Trials databases. The meta-analysis was performed using Review Manager and Stata/SE software. The outcomes were changes in renal function and serum uric acid (SUA), creatinine, and adverse events. Results: Twelve RCTs with 1469 participants were included in the meta-analysis. ULT was found to effectively lower SUA (standard mean difference (SMD): -2.70; 95% confidence interval (CI): -3.71, -1.69) but the renoprotective effects were not superior to those of control therapy (placebo or usual therapy), which were stable in the subgroup analyses and sensitivity analyses. Regarding adverse events, their risks did not increase in the ULT group compared with the control group and were stable in the sensitivity analyses. Conclusion: The findings of our meta-analysis suggested that ULT can effectively lower SUA, but there is insufficient evidence to support the renoprotective effects of ULT in CKD patients. In addition, ULT is safe for patients with CKD.